2013
DOI: 10.1016/j.cej.2013.06.118
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biomass-based carbon adsorbents for post-combustion CO2 capture

Abstract: Sustainable carbon adsorbents have been produced from biomass residues by single-step activation with CO 2 . The activation conditions were optimised to develop narrow micropores in order to maximise the CO 2 adsorption capacity of the carbons under post-combustion conditions. The equilibrium of adsorption of pure CO 2 and N 2 was measured between 0 and 50 ˚C up to 120 kPa for the outstanding carbons. The CO 2 adsorption capacity measured at low pressures is among the highest ever reported for carbon materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(143 citation statements)
references
References 42 publications
12
128
1
Order By: Relevance
“…For effective capture and removal of the CO 2 , high selectivity and adsorption capacity of absorbents are required, in addition to their durability in time, low cost, and ease of regeneration. (Bio)char-based activated carbons have shown adsorption capacity similar to the highest reported for other carbon materials [63].…”
Section: (Bio)char As Gas Adsorbentsupporting
confidence: 56%
“…For effective capture and removal of the CO 2 , high selectivity and adsorption capacity of absorbents are required, in addition to their durability in time, low cost, and ease of regeneration. (Bio)char-based activated carbons have shown adsorption capacity similar to the highest reported for other carbon materials [63].…”
Section: (Bio)char As Gas Adsorbentsupporting
confidence: 56%
“…Biochar can also be applied as soil amendment to increase soil quality, reduce greenhouse gas emission, and as a sorbent to remove organic and inorganic contaminants from soil and water [152]. Biocharbased activated carbon has shown promising results as a gas adsorbent to capture and store carbon dioxide [58] and hydrogen [94]. Biochar also has the potential to replace coal in direct carbon fuel cell systems (DCFC) [49,79].…”
Section: Products Of Pyrolysismentioning
confidence: 99%
“…Typical concentration levels range between 12% and 14% for coal-fired boilers and integrated gasification combined cycles (IGCC), 11-13% for oil-fired boilers, 3-4% for gas turbines, and 7-10% for natural gas fired boilers [2]. It has been widely shown that cost-effective mitigation of CO 2 emissions from these electricity-generating sources can be accomplished by carbon capture and storage (CCS) [3][4][5][6][7][8][9][10] The separation of CO 2 from post-combustion flue gas can be conducted by various approaches, including physical/chemical absorption [11][12][13][14][15][16][17][18][19][20][21], adsorption [22][23][24][25][26][27][28][29][30][31], membrane separation [32][33][34][35][36][37][38][39][40][41][42][43][44], and cryogenic distillation [45][46][47]…”
Section: Introductionmentioning
confidence: 99%